Multimodal SEL Interventions in Preschool Settings: A Review of Methodologies and Measured Outcomes - Hikmah Munawaroh; Asep Supena; Sri Indah Pujiastuti (Civiliza Publishing, Indonesia., 2026)
Social-Emotional Learning (SEL) interventions in preschool settings are increasingly recognized as foundational for children's holistic development, fostering crucial skills in emotional regulation, social interaction, and school readiness. This systematic literature review aimed to examine methodologies, measured outcomes, and implementation strategies of multimodal SEL interventions globally between 2016 and 2025. Utilizing Scopus as the primary database, the review applied rigorous inclusion and exclusion criteria, resulting in the analysis of empirical studies evaluating diverse SEL modalities, teacher professional development (PD), and cultural adaptations. Results revealed significant positive impacts from multimodal SEL interventions, including mindfulness practices, play-based learning, digital approaches, and parent involvement, across various developmental domains such as emotional competencies, social skills, and academic performance. Notably, structured and ongoing teacher PD emerged as essential for ensuring high program fidelity and effective SEL delivery. Culturally responsive adaptations were identified as critical factors enhancing program relevance and acceptance, especially in multilingual and multicultural contexts. Despite these promising findings, methodological variability and inconsistencies in measuring long-term impacts indicate a pressing need for standardized approaches and more rigorous longitudinal research. The study provides compelling evidence supporting integrative theoretical frameworks by CASEL, Vygotsky, and Bronfenbrenner, advocating holistic and contextually responsive SEL implementation. Key implications include prioritizing comprehensive teacher training, community and family engagement, and culturally adaptive curricula. Future research directions emphasize the importance of longitudinal studies, consistent fidelity assessments, and broader representation of diverse global contexts to enrich the SEL literature and practice.